1999
DOI: 10.1007/s002469900416
|View full text |Cite
|
Sign up to set email alerts
|

Turner's Syndrome: Cardiologic Profile According to the Different Chromosomal Patterns and Long-Term Clinical Follow-Up of 136 Nonpreselected Patients

Abstract: The preferential association between Turner's syndrome and congenital heart defects (CHD) have been well known since the first description by Morgagni. There are few studies about the different cardiologic problems stemming from different chromosomal patterns of X monosomies. We reviewed a large series of 136 patients with Turner syndrome without cardiologic preselection, 29 of whom had some kind of CHD (21.5%). Partial anomalous pulmonary venous drainage (PAPVD; 2.9%), aortic valve disease (stenosis and/or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 28 publications
(40 reference statements)
3
47
1
1
Order By: Relevance
“…10 In sonographically evaluated studies, the prevalence ranged from 17 to 26%. 1,3,11,12 In this study we found at least one cardiovascular anomaly (CVA) in 29.9%. Since all patients with cytogenetically diagnosed UTS attended either our endocrinologic or cardiologic outpatient department, there may be a potential bias, inherent in most hospital-based studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…10 In sonographically evaluated studies, the prevalence ranged from 17 to 26%. 1,3,11,12 In this study we found at least one cardiovascular anomaly (CVA) in 29.9%. Since all patients with cytogenetically diagnosed UTS attended either our endocrinologic or cardiologic outpatient department, there may be a potential bias, inherent in most hospital-based studies.…”
Section: Discussionmentioning
confidence: 89%
“…This finding and the usually not excludable presence of mosaicism make planning of phenotype mapping studies difficult. 1,3,12,16,17 Zinn et al investigated 28 Xp-females (age range 1.3-41.5 years), mapping deletions by fluorescent in situ hybridization (FISH) for several phenotypic features; none of them had CVA. 17 The short stature homeobox gene (SHOX) is the first and best gene described to be involved in UTS phenotype features.…”
Section: Discussionmentioning
confidence: 99%
“…14 Both coarctation and bicuspid aortic valve occur more frequently in men, with a prevalence of approximately 4:1. A high prevalence of these same lesions is found in Turner syndrome, 15 a sex aneuploidy syndrome caused by the complete absence of a sex chromosome or the presence of a structurally abnormal one. Structural cardiac anomalies are most prevalent in those women with pure 45X monosomy than in those with an isochromosome Xq karyotype 16 and when Turner patients are compared with the general population, aortic valve disease occurs 146 times more commonly.…”
Section: Aortic Outcomesmentioning
confidence: 84%
“…In some way these neuroectodermal immigrants may influence medial degeneration and cause both aortic dilatation and cerebral aneurysm. http://heart.bmj.com/ lesions is also found in women with Turner's syndrome 14 -a sex aneuploidy syndrome caused by the complete absence of an X chromosome or the presence of a structurally abnormal one. Thus, since aortic disease is mainly a "male domain" and the absence of a normal second X chromosome is associated with aortopathy, one might speculate that a genetic factor that modulates the development of the aorta and valve might be located on the X chromosome.…”
Section: Coarctation: a Diffuse Arteriopathymentioning
confidence: 99%